Current and emerging trends in bioaugmentation of organic contaminated soils: A review. (15th October 2022) - Gao, Dawen; Zhao, Huan; Wang, Litao; Li, Ying; Tang, Teng; Bai, Yuhong; Liang, Hong
Abstract: Organic contaminated soils constitute an important environmental problem, whereas field applicability of existing physical-chemical methods has encountered numerous obstacles, such as high chemical cost, large energy consumption, secondary pollution, and soil degradation. Bioaugmentation is an environmentally friendly and potentially economic technology that efficiently removes toxic pollutants from organic contaminated soils by microorganisms or their enzymes and bioremediation additives. This review attempted to explore the recent advances in bioaugmentation of organic contaminated soils and provided a comprehensive summary of various bioaugmentation methods, including bacterial, fungus, enzymes and bioremediation additives. The practical application of bioaugmentation is frequently limited by soil environmental conditions, microbial relationships, enzyme durability and remediation cycles. To tackle these problems, the future of bioaugmentation can be processed from sustainability of broad-spectrum bioremediation carriers, microbial/enzyme agents targeting combined contaminants, desorption of environmentally friendly additives and small molecular biological stimulants. Findings of this research are expected to provide new references for bioaugmentation methods that are practically feasible and economically potential. Graphical abstract: Image 1 Highlights: Fungi and their secreted enzymes, with non-specific and catalytic power, have tremendous potential in bioaugmentation. Mechanisms involved in bioaugmentation are still not well known and needs further studies. Soil type, microbe competitions, enzyme inactivation limited the application of bioaugmentation. Perspectives on microbial agents, immobilization, desorption additives and biological stimulants were stressed.